Application of PJBL-STEAM and PBL STEAM learning models; improving cognitive learning outcomes, creative thinking and critical thinking of junior high school students inTanimbar Islands Regency - Elwuar, Susan; Rumahlatu, Dominggus; Liline, Sintje (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2024)
STEAM learning is one of the learning innovations that can be applied because it is able to develop 21st century skills. Based on this, the learning models that can be combined with the STEAM approach are project based learning (PjBL) and problem based learning (PBL). The aim of this research is to determine the influence of the PjBL STEAM learning model on cognitive, creative thinking and critical thinking learning outcomes and the influence of the PBL STEAM learning model on cognitive, creative thinking and critical thinking learning outcomes of junior high school students in Tanimbar district. This type of research is quasi-experimental research. The population is all students of SMP Negeri 1 Tanimbar Selatan, SMP Negeri 2 Tanimbar Selatan and SMP Negeri 1 Tanimbar Utara in the even semester of the 2023/2024 academic year with the sample being class VII. Data analysis usingAncova and continued with the LSD test with the help of SPSS Version 27. The research results show thatThere is influencePjBL STEAM learning model on the cognitive, creative thinking and critical thinking learning outcomes of junior high school students in the Tanimbar Islands Regency with a sig value < 0.05 and there is an influence of the PBL STEAM learning model on the cognitive, creative thinking and critical thinking learning outcomes of junior high school students in the Tanimbar Islands Regency with a value sig < 0.05